Montaigne, Hobbes, and Bayle on the Archaeology of Religion. Issue 2 (2nd July 2016) - MacPhail, Eric
Abstract : This article proposes a comparison between Michel de Montaigne, Thomas Hobbes, and Pierre Bayle on the basis of their common understanding of the origin of religion, an understanding that can be called an archaeology of religion. The key to the comparison is the reading of Montaigne's chapter 'Des boyteux' (III, 11) offered by Bayle in his Pensées diverses sur la comète, a reading that presupposes the argument laid out in Chapter 12 of Hobbes's Leviathan . The article suggests some creative tension between these three texts in respect of a major topic of early modern thought: political theology.